Fancy Nancy : fancy day in room 1-A - O'Connor, Jane (O'Connor, Jane. Fancy Nancy., 2012)
To cheer up her classmates after a gloomy week, Nancy thinks of a new celebration, Fancy Day, but when the day arrives Ms. Glass shows up without her fancy dress, and the class must think of a way to make her as elegant as everyone else.